Key establishment protocols for secure communication in clustered sensor networks. (1st January 2013) - Poornima, A.S.; Amberker, B.B.
Clustering in wireless sensor networks (WSN) is a technique used to improve the lifetime of the network. Heinzelman et al. proposed a clustering method called LEACH which rotates the role of CH among the nodes in the network. However, it does not provide any security. In this paper, we propose two deterministic key establishment protocols to counter the vulnerabilities of LEACH protocol. These protocols are called polynomial based key establishment protocol (PBKEP) and hash-based key establishment protocol (HBKEP). These protocols ensure that it is always possible to establish a secret key with the current CH in every round of LEACH clustering protocol. The protocols also ensure that a malicious node cannot join the cluster at any round. The clusters are formed only among the legitimate nodes. Also any malicious node pretending as CH will not succeed as no other legitimate node will choose that as CH.